Implementing OBE to Innovate Entrepreneurship Education in Higher Education - Dewiana Novitasari; Yulis Nuryanti; Multi Nadeak; Hatoli Waruwu; Masduki Asbari (Yayasan Aya Sophia Indonesia, 2024)
This project focuses on translating Outcome-Based Education (OBE) policy into learning design, execution, and assessment of learning outcomes in higher education entrepreneurial courses. Case study-based qualitative research is used in this study. Data were collected via extensive interviews with lecturers, students, and institutional policymakers, observation of entrepreneurship course learning, and assessment of Semester Learning Plan (SSP) and learning outcomes evaluation materials. Data was analyzed using thematic analysis to find patterns and correlations. The research shows that lecturers understand OBE principles and practises well enough to create learning outcomes, use experiential learning methods like business simulations and collaborative projects, and create relevant evaluation tools. This understanding helps lecturers integrate the OBE policy into the curriculum, improving student creativity, inventiveness, and problem-solving. This technique was successful, but institutional backing remains an issue. Limitations include limited resources, a need for creative evaluation tools, and poor instructor-student communication about OBE-based learning objectives. Students believe OBE-based learning is relevant to professional life, although the intensive exercises require better time management. This study improves theoretical comprehension of OBE policies in practice-oriented courses like entrepreneurship. This research emphasizes the need for continued lecturer training, a more detailed policy implementation guide, and additional resources to improve learning. The paper recommends more research on OBE policy's long-term effects on graduate quality and labor market alignment.